Mobility for learners and staff - higher education students and staff mobility inter-institutional agreement 2014-20[21] between programme countries - Bauhaus-Universität Weimar and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2015)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme. - Subject area: Architecture